Delavci - zunanji izvajalci? - Senčur Peček, Darja (Delavci in delodajalci, 2012)
The authoress discusses some current issues regarding the outsourcing. She focuses on the different legal position of the employees who were formerly employed by the employer. One of them is transfer of the undertaking. The most important question in the case of transfer of the services is, when the economic entity retains its identity. Very common is also the situation where the employer contract-out certain activity to the former employee. This category of economically dependent workers needs certain labour-law protection. Special problem are triangle relationships between user, provider of the service and employee, where the question of the true employer arises.
Keywords: delovno pravo; organizacija dela; podjetja; pogodbeni izvajalci; storitve; zunanji izvajalci